INVESTIGATION OF THE RELATIONSHIP BETWEEN REGISTERED ECONOMY AND UNREGISTERED EMPLOYMENT RATE BY SECTORS IN TURKEY (Third Sector Social Economic Review, 2022)
There are many empirical studies on the determination of explanatory factors of economic growth. Since the 1970s, the interest in unregistered economy has started to increase and it has been focused on investigating the effects of unregistered economy on registered economy. It is suggested that unregistered economy and, accordingly, unregistered employment have negative and positive effects on registered economy. In this context, in this study, the aim is estimation of an optimal unregistered employment rate for total economy, agriculture, services and industry in Turkey. Analyzes were carried out using a panel data set covering 2009-2020 and NUTS 2 level. In order to determine the optimal unregistered employment rate for Turkey, whether the inverted U form is valid or not, unlike other studies in the literature, it has been investigated to consider both sectors and regional differences by using four different dynamic panel data models. These dynamic panel data models estimated by Arrellona and Bond (1991)’s method. The findings show that the inverted U form is valid for total economy and industrial. However, no significant relationship was found between unregistered employment and agricultural. Also, it is determined that there is a linear relationship between services and unregistered employment. Optimum unregistered employment rates were estimated as 66.21% for total economy and 66.46% for industry.
Keywords: Unregistered employment; economic growth; sector analysis; dynamic panel data analysis; Arrellona and Bond estimate method.